1993
DOI: 10.1111/j.1476-5381.1993.tb13702.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine‐induced decreases in the inward rectifier potassium and the inward calcium currents in rat ventricular myocytes

Abstract: The effects of high (20 mm) concentrations of caffeine were studied on the transmembrane voltage and currents in rat single ventricular myocytes by the whole cell configuration of the patch clamp technique. Rapid application of caffeine released Ca2+ from the sarcoplasmic reticulum and induced a Ni2+‐sensitive transient inward current with concomitant change of the transmembrane voltage from −72.6 ± 0.4 to −68.0 ± 0.6 mV (n = 4). Maintained application of caffeine lengthened the action potential duration (APD9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…The SR Ca 2ϩ content was evaluated by rapid application of 10 mM caffeine to release the stored Ca 2ϩ , and the resultant Ca 2ϩ transient was measured (29). When assessed 45 s after photolysis of 5 M caged-NAADP, the Ca 2ϩ signal caused by rapid application of 10 mM caffeine was significantly increased by 21 Ϯ 4% (Fig.…”
Section: Effects Of Photolysis Of Caged Naadp On Whole Cell Ca 2ϩmentioning
confidence: 99%
“…The SR Ca 2ϩ content was evaluated by rapid application of 10 mM caffeine to release the stored Ca 2ϩ , and the resultant Ca 2ϩ transient was measured (29). When assessed 45 s after photolysis of 5 M caged-NAADP, the Ca 2ϩ signal caused by rapid application of 10 mM caffeine was significantly increased by 21 Ϯ 4% (Fig.…”
Section: Effects Of Photolysis Of Caged Naadp On Whole Cell Ca 2ϩmentioning
confidence: 99%
“…Caffeine has been reported to inhibit potassium channels in a number of cell types, including mammalian ventricular myocytes (Sanchez-Chapula, 1992;Varro et al, 1993;Cui and Terrar, 1995;Chorvatova and Hussain, 2003), smooth muscle cells (Noack et al, 1990;Teramoto et al, 2000), dissociated chick autonomic ganglion neurons and pineal cells (Reiser et al, 1996), taste receptor cells (Zhao et al, 2002) and rat anterior pituitary cells (Kramer et al, 1994). Theophylline, too, has been shown to modulate potassium channels (Yamamoto et al, 1995;Schroder et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A structurally related methylxanthine, IBMX, also caused inhibition of voltage-activated K+ currents in chick ciliary ganglion neurones at millimolar concentrations. Previous studies have shown that millimolar concentrations of caffeine inhibit voltage-dependent K+ currents in rat ventricular myocytes (Sanchez-Chapula, 1992;Varro et al, 1993) and guinea-pig portal vein (Noack et al, 1990), although these effects were not described in detail. IBMX has been shown to inhibit a voltage-activated tetraethylammonium-sensitive K+ current in rat sensory neurones (Usachev et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical properties of the caffeine-sensitive K+ channels are clearly different in some of these cell types. For example, one of the caffeine-sensitive currents in ventricular myocytes is a Ba2+ -sensitive inward rectifier (Varro et al, 1993). This suggests a direct effect on conserved pore regions of the channel molecules as it is unlikely that the same regulatory cascades could result in blockade of K+ channels in all of these preparations (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation